KEJAHATAN DEFECTING: Studi Perbandingan antara Undang-Undang ITEdan Hukum Pidana Islam - Muyasir, Ahmad (UIN Sunan Kalijaga Yogyakarta, 2015)
As the technology advances, the crimeis no longerjusthappeningin the real world, but itis alreadyreaching into thevirtual worldor virtual. In this case, defacing a form of cyber crimes is quite disturbing and has hurt many people. Heiscybercrimeisdone bychanging thelook of the websiteof a website, eitherin part orseeluruhnyabyfirstlybreaking intoanother person, withoutthe owner's permission.This paper isgoing toexaminethe phenomenonof cyber crime(cyber crime), along withbetuk, motives, consequences, andlegal sanctions.In this paper, the problem of evildefectingwill beassessedfrom the perspective ofthe Indonesian CriminallawandIslamic Criminallaw(Fiqh Jinayah).